-
The value of cos π - θ cos π - ∅ -sin π - θ sin π - ∅ will be 4 4 4 4
-
- sin(θ – ∅)
- sin(θ + ∅)
- cos(θ – ∅)
- cos(θ + ∅)
- sin(θ – ∅)
Correct Option: B
Here,
cos | ![]() | - θ | ![]() | cos | ![]() | - ∅ | ![]() | ||
4 | 4 |
- sin | ![]() | - θ | ![]() | sin | ![]() | - ∅ | ![]() | = ? | ||
4 | 4 |
Let
- θ = A | |
4 |
- ∅ = B | |
4 |
⇒ cos | ![]() | - θ | ![]() | cos | ![]() | - ∅ | ![]() | ||
4 | 4 |
- sin | ![]() | - θ | ![]() | sin | ![]() | - ∅ | ![]() | = ? | ||
4 | 4 |
= cos | ![]() | - θ + | - ∅ | ![]() | ||
4 | 4 |
= cos | ![]() | - θ - ∅ | ![]() | |
2 |
= cos | ![]() | - (θ + ∅) | ![]() | |
2 |
= sin (θ + ∅)
∵ cos | ![]() | - θ | ![]() | = sinθ | |
2 |